Requirements and potential for enhanced EVA information interfaces - Hodgson,E; Sidgreaves,R; Braham,S; Hoffman,J; Carr,C; Lee,P; Marmolejo,J; Miller,J; Rosenberg,I; Schwartz,S (2003)
NASA has long recognized the advantages of providing improved information interfaces to EVA astronauts and has pursued this goal through a number of development programs over the past decade. None of these activities or parallel efforts in industry and academia has so far resulted in the development of an operational system to replace or augment the current extravehicular mobility unit (EMU) Display and Controls Module (DCM) display and cuff checklist. Recent advances in display, communications, and information processing technologies offer exciting new opportunities for EVA information interfaces that can better serve the needs of a variety of NASA missions. Hamilton Sundstrand Space Systems International (HSSSI) has been collaborating with Simon Fraser University and others on the NASA Haughton Mars Project and with researchers at the Massachusetts Institute of Technology (MIT), Boeing, and Symbol Technologies in investigating these possibilities. The objectives of this research so far have been to better understand the ways in which an improved information interface may be applied in a variety of mission settings and to refine the definition of system design requirements to best support those applications. Research efforts have combined the results of concept definition and mission requirements studies with experiments in pressurized spacesuits in the laboratory and in lower fidelity test-beds in field settings. Several promising approaches for the integration of highly capable information interfaces with EVA systems have evolved and have been evaluated in preliminary proof-of-concept tests. The results show considerable promise that an advanced information interface could be adapted to support near-term orbital EVA missions and could be evolved to provide robust support for future planetary exploration missions. Copyright © 2003 Hamilton Sundstrand Space Systems International, Inc.